PERANCANGAN DESIGN UI/UX WEBSITE HOUSE OF NEGATIVE MENGGUNAKAN METODE DESIGN THINKING - Putra, Gilang Adi; Utami, Putri Yuli; Istikoma, Istikoma (Politeknik Bisnis Indonesia, 2025)
House of Negative is an independent music label established in 2019, engaged in the production and distribution of diverse musical works. This study focuses on the design of the user interface (UI) and user experience (UX) of the House of Negative website using the Design Thinking approach. The objective is to develop an interface that is both intuitive and user-friendly, thereby improving user interaction with the label and its associated content. The stages of Design Thinking were implemented to identify user needs and formulate appropriate design solutions. The resulting prototype was evaluated using the System Usability Scale (SUS), which produced a usability score of 87.25, classified in the “excellent” category and exceeding the standard of the previous application. These results indicate that the Design Thinking methodology is effective in generating UI solutions that are functional, relevant, and user-centered. The intended users of the website include musicians and the general public; the former is facilitated in managing their musical portfolios and audience engagement, while the latter are provided with a platform for discovering new music and interacting within the broader music community.